Sonoelectrochemistry at platinum and boron-doped diamond electrodes: achieving 'fast mass transport' for 'slow diffusers' - Holt, K; Del Campo, J; Foord, J; Compton, R; Marken, F (2001)
It is demonstrated for electrochemical processes in aqueous solution enhanced by ultrasound from a glass-horn transducer (24 kHz, 8 W cm-2) that the mass transport limited current is essentially independent of the diffusion coefficient. An explanation is proposed for this phenomenon, which allows, at low ultrasound power, considerable enhancements of the mass transport of 'slow diffusers' with small D, to be achieved via interfacial cavitation. An application of this effect in the anodic destruction of an aqueous Procion Blue dye solution at boron-doped diamond electrodes is discussed. © 2001 Elsevier Science B.V. All rights reserved.